Perspectives of usage of seamless and fiber basalt filament for construction and rehabilitation of motor roads and airfields - Krayushkina, Kateryna; Bieliatynskyi, Andrii (International Conference “Environmental Engineering”, 2020)
In recent years, the number of heavy vehicles has increased on the roads of Ukraine. But coatings that were built long ago and according to the old standards do not withstand overhauls. This leads to premature destruction of the road structure, which is also facilitated by negative weather factors. One of the ways to increase the durability of roads is the use of dispersed and directional reinforcement with basalt materials. The article presents the results of studies on the use of basalt materials for reinforcing asphalt concrete and concrete coatings of aerodrome roads.
Keywords: fibers; crack; asphalt; concrete; reinforced; pavement; grids; road construction